Tracking decision-making of backcountry users using GPS tracks and participant surveys. (July 2022) - Hendrikx, Jordy; Johnson, Jerry; Mannberg, Andrea
Abstract: Snow avalanches are a significant natural hazard representing the primary risk of death to backcountry travelers in many alpine countries. Careful use of backcountry terrain through effective decision making can mitigate the risk of dangerous snowpack conditions, but requires relevant knowledge and experience. We present the results from a large-scale crowd sourced data collection method from backcountry users. Using GPS tracking via a smartphone application, coupled with online surveys, we investigate the intersection of geographical complexity, backcountry experience, demographics and behavioral biases on decision-making while navigating hazardous winter terrain. We use data from 770 GPS tracks, representing almost 1.3 million GPS points, as a geographic expression of a group's resulting decisions, and use them to quantify and understand their decision-making process. Our analysis focuses on the change in terrain use as quantified using the Avalanche Terrain Exposure Scale (ATES), and time spent in avalanche terrain, as a function of experience, avalanche hazard and other group factors. We show that self-identified experts rate themselves as significantly more skilled and also had higher levels of avalanche education. Experts also had an increased exposure to avalanche terrain overall, and also more severe terrain, as represented by median time in class 3 ATES terrain. Highlights: Crowd-sourced GPS tracking provided insights to back-country travel in avalanche terrain. The Avalanche Terrain Exposure Scale provides a powerful metric to assess decision-making and terrain use. Combined surveys and GPS tracking provide geographic expression of real world decision-making. Experience impacts decision making processes and resultant terrain use.